Application of Restorative Justice Against Abuse of Children with Disabilities: Penerapan Restorative Justice Terhadap Penganiayaan Anak Penyandang Disabilitas - Sianturi , Mekarinta (LPPM UPMI, 2023)
This study aims to analyze the legal protection of children with disabilities who are in conflict with the law according to Indonesian laws and regulations and the application of the concept of diversion for children with disabilities who commit acts of violence. This research is motivated by the lack of research on the application of restorative justice to children with disabilities. The novelty of this research is that there is no research that discusses the application of restorative justice for children with disabilities who are in conflict with the law as perpetrators of violent crimes. The research method used is juridical-normative with a statutory approach (statute approach) and a conceptual approach (conceptual approach). Results the research concludes that first, for the purposes of examining the legal process, children with disabilities have the right to receive assistance from the family or companion concerned. Second, the application of restorative justice can be applied to cases of violence committed by children with disabilities starting from the stages of investigation, prosecution, to the judicial process in the District Court.